Does R&D investment in renewable energy technologies reduce greenhouse gas emissions? - Hailemariam, Abebe; Ivanovski, Kris; Dzhumashev, Ratebek (Elsevier, 2022)
In this paper, we investigate the impact of public investment in R&D in renewable energy technologies on environmental quality using a spectrum of environmental emissions. We employ new and innovative panel data methods to address the existing econometric issues in estimating the effect of R&D on greenhouse gas emissions. Then, using data from advanced and emerging economies that span the period from 1980 to 2020, we find that R&D investment in renewable technologies has a significant positive effect on environmental quality by reducing a range of pollutants, including carbon dioxide, methane, and other pollutants. The results are robust to a series of sensitivity tests. The findings have important policy implications for climate change and various recent environmental initiatives, including the transition to net-zero emissions and sustainability.